2004
DOI: 10.1007/s10653-005-5361-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mining activities on soils in a semi-arid environment: Sierra Almagrera district, SE Spain

Abstract: Field and laboratory-column studies were undertaken in order to investigate soil contamination derived from past mining activity in the Sierra Almagrera (SA) district in southeast Spain. The tailings, soil and sediment samples that were collected showed high concentrations of Ag, As, Ba, Cu, Pb, Sb and Zn when analyzed. The mean concentrations of these elements in the tailings were 29.8, 285.4, 54000, 57.7, 2687.5, 179.0 and 2269.0 ppm, respectively. In the soil samples these decreased to 14.3, 96.9, 24700, 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…Various analysis techniques, sampling and modeling schemes have been proposed and applied by researchers and according to Cuccu (2002), judgmental sampling, systematic and regular grid sampling, simple random sampling, stratified sampling, ranked set sampling, composite sampling can all be used as sampling method, and the techniques to achieve sampling operations may differ in function of number of sampling area and geometric features of sampling location. Navarro et al (2004) have carried out field and laboratory studies in order to investigate soil contamination derived from past mining activity in the Sierra Almagrera district in…”
Section: Xinmentioning
confidence: 99%
“…Various analysis techniques, sampling and modeling schemes have been proposed and applied by researchers and according to Cuccu (2002), judgmental sampling, systematic and regular grid sampling, simple random sampling, stratified sampling, ranked set sampling, composite sampling can all be used as sampling method, and the techniques to achieve sampling operations may differ in function of number of sampling area and geometric features of sampling location. Navarro et al (2004) have carried out field and laboratory studies in order to investigate soil contamination derived from past mining activity in the Sierra Almagrera district in…”
Section: Xinmentioning
confidence: 99%
“…The area comprising the Sierra Almagrera (Figure 1), located 90 km NE of the city of Almerí a (SE Spain), together with the Iberian Pyrite Belt and the Cartagena mining district, is the oldest metallurgical and mining area in the Iberian Peninsula [33][34][35]. During the nineteenth century and the early twentieth century, the smelting plants located along the Mediterranean coastline of the Sierra Almagrera district produced approximately 550,000 t of Pb and 3000 t of Ag.…”
Section: Research Sitementioning
confidence: 99%
“…168 water table is generally located 20-30 m below the surface, 169 with annual and seasonal oscillations (Navarro et al 2004). …”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In addition, distilled water extracts from these 404 tailings indicated that the extractions were saturated to 405 supersaturated with calcite, dolomite, gypsum, jarosite, and 406 iron oxyhydroxides (Navarro et al 2004). Pore water sat-407 uration, with respect to jarosite, natrojarosite, and gypsum 408 McGregor et al 1998), and the possible 409 mobilization of metals from oxyhydroxides and sulfates, 410 have been detected in other tailings areas.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation